Fiqh Mu’āmalah Content in Friday Sermon: Dialectics of the Mosque as a Ritual Space and the Market as Economic Space - Musahadi Musahadi (Al-Ahkam, 2021)
This paper describes fiqh mu’āmalah content in Friday sermons at the Great Mosque of Kauman Semarang to understand the dialectics between the mosque as a ritual space and the market as an economic space. This paper's data are in the form of 51 sermons delivered in 2015 from January 1 to December 31, 2015, and interviews with the foundation, ta’mīr, and the preachers. This paper shows that Friday sermons' characteristics at the mosque are reflected in their preachers' diversity, both in terms of educational background, scientific fields, organizational affiliations, and professions. This paper finds that fiqh mu’āmalah's content has not become the point of attention of the preachers. This finding is proven by the absence of a sermon theme on fiqh mu’āmalah (mu’āmalah madiyah). The topic that appeared in Friday's sermon was related to Islamic economics's ethical principles and business-related to mu’āmalah adabiyah. The minimal content of fiqh mu’āmalah or economic fiqh in the Friday sermon of the mosque reflects the low intensity of the mosque's dialectics as a ritual space with the market as an economic space. The Friday sermon at this mosque still does not pay more attention to the jamā’ah of Johar market seller as the essential segment.